Cooperative fencing control of multiple second‐order vehicles for a moving target with and without velocity measurements. (16th March 2021) - Kou, Liwei; Huang, Yi; Chen, Zhiyong; He, Shiming; Xiang, Ji
Abstract: This article studies the moving‐target‐fencing problem of multiple second‐order vehicles, where the target moves with an unknown constant velocity. Without a predefined stand‐off distance or formation, two classes of local cooperative controllers are proposed with and without velocity measurements. Specifically, the first controller uses the relative position information from the target and vehicle's neighbors, as well as the vehicle's velocity measurement, while the second controller relaxes the common requirement of velocity measurement of the vehicles. It is proved that both controllers simultaneously assure target fencing, collision avoidance, and velocity convergence. Finally, numerical simulations are provided to verify the efficacy of the proposed controllers.